DYNAMICS OF UNEMPLOYMENT IN THE DISTRICT JOMBANG: ANALYSIS ON POPULATION, EDUCATION, AND GROWTH ECONOMY (2018-2020) - Nurhayati, Wina; Khoiruddin, Khoiruddin (PT. Altin Riset Publishing, 2023)
Study This aims to determine the effect of population, education level and economic growth on the unemployment rate in Jombang Regency in 2018-2020, based on the type of relationship between variables, this research is included in the causal relationship of the variables that cause unemployment, while seen from the unit of analysis used . carried out, this research uses a group analysis unit with multiple regression analysis. This research aims to determine the effect of the resulting population, the level of education and economic growth have a simultaneous influence on unemployment in Jombang Regency. This means that the higher or lower the population, level of education and economic growth in Jombang Regency will simultaneously influence unemployment in Jombang Regency in 2018-2020.